Mania as a Rare Adverse Event Secondary to Steroid Eye Drops - Moayyad Alsalem; Majed A. Alharbi; Rayan A. Alshareef; Raghad Khorshid; Salman Thabet; Abdulrahman Alghamdi (Case Reports in Psychiatry)
Since glucocorticoids (GCs) were introduced for the treatment of various diseases, they have been linked with the development of psychiatric adverse effects such as mania, depression, and psychosis. These behavioral or psychiatric adverse events usually appear within a few days after commencing GCs and are possibly to reverse with drug withdrawal. We present a rare case of a 75-year-old woman who developed mania during treatment with GC eye drops following cataract surgery. Management consisted of discontinuing prednisolone and administering olanzapine, which resulted in full recovery in a week. Olanzapine was then discontinued, and a diagnosis of steroid-induced mania was concluded for this case.